Language Style Used in Commercial Advertisement Text on Social Media - Kadek Ayu Kartika Septiana; Ngurah Artha Yoga Pratama; Ni Putu Ayu Kartika Sari Dewi (RETORIKA: Jurnal Ilmu Bahasa, 2023)
The aims of the research are describing the language style found in commercial advertisements text on social media based on the word choice, the sentence structure, and the implicit meaning. The data in this research are 15 commercial advertisements which are divided into three categories those are food, beverage, and cosmetic advertisements, and were taken from social media such as Instagram, Facebook, and YouTube. The methods and techniques used in collecting the data are the observation method followed by Simak Bebas Libat Cakap (SBLC) technique (Uninvolved Conversation Observation Technique) and the note-taking technique. In analyzing the data, padan ortografis method (orthography corresponding method) is used and supported by dasar pilah unsur penentu technique (determinant-sorting technique). In presenting the results, informal methods are used. The result of the research shows that there are 14 language styles found in 15 commercial advertisements on social media. Based on the word choice, all of the advertisements used an informal style. Based on the sentence structure, the advertisements used a repetition style. Based on the implicit meaning, the advertisements used rhetorical style included alliteration, asyndeton, ellipsis, pleonasm and tautology, rhetorical question, epanorthosis, and hyperbole and the figurative style included simile, personification, epithetic, synecdoche, and antonomasia.